PREVALENCY OF FASCIOLIASIS IN LLAMAS AND ALPACAS IN TWO RURALCOMMUNITIES OF JAUJA, PERU - Flores C., Benjamin (2014)
The aim of this study was to determine the prevalence and parasite load of Fasciolahepatica in llamas and alpacas of 12-48 months of age in the districts of Masma Chiccheand Llocllapampa, Jauja, Peru, and to determine the association between the prevalenceof F. hepatica with sex and age. Two hundred fecal samples were collected from llamas (n= 97) and alpacas (n= 103) in October 2011. The samples were analyzed by thespontaneous sedimentation technique and the parasite load by the modified McMastermethod. The prevalence of F. hepatica in llamas was 49.5% and in alpacas was 73.8%without statistical differences due to sex and age. The parasite load was 12.6 and 19.9eggs per gram of faeces (epg) in llamas and alpacas respectively.